Practical Problems and Solutions in Junior High School Physical Education from a Stakeholder Perspective - Xiao, Xianghan; He, Linghui; Li, Chen; Hu, Yangyan (Quality in Sport, 2026)
Research Background and Purpose: Despite educational reforms promoting holistic development, junior high physical education in China remains heavily exam-oriented. This study applies stakeholder theory to identify key actors, analyze their interests, and propose strategies to reduce test-driven practices. Research Methods: Through literature review and logical analysis, we examine the development of stakeholder classification models and assess their relevance to physical education, while also investigating the root causes of current problems in the field. Research Results: The study identifies four phases in stakeholder theory: initial exploration (1980–1990), deepening development (1990–2000), steady advancement (2000–2010), and innovative breakthrough (2010–2025). Significant test-oriented tendencies were observed in junior high physical education across teaching objectives, content, methods, assessment, and broader sociopolitical dimensions. Key contributing factors include grade-driven instruction, limited awareness among schools and teachers, narrow assessment criteria, and cultural-academic pressures. Research Conclusions: Proposed solutions emphasize shifting toward game-based and life-relevant content, adopting scientific and personalized teaching methods, and diversifying evaluation mechanisms. Aligning the core interests of stakeholders at both macro-policy and micro-practice levels is essential to restoring physical education’s fundamental role in supporting students’ holistic development. Research Value: Theoretically, this work expands stakeholder theory into physical education, offering a systematic lens for understanding complex educational interactions. Practically, it provides a actionable framework to help policymakers, administrators, and teachers better allocate resources and reform teaching practices, supporting a shift toward student-centered physical and mental development.